Application of planning software in construction industries : study on effectiveness of planning software toward project planning - Ain Rashida, Abdullah (2016)
The construction industry is significant in the development of the Malaysian economy towards fully developed nation. To implement construction project, a proper planning and scheduling is of vital important in order for the project to be executed and run smoothly. The best schedule is not the schedule showing the project completed in the shortest time period, it is the schedule that meets the primary objectives of the total project. Those primary objectives are to create a quality project, completed on time, within budget, and in a safe work environment. Therefore, this is focus on research to study on effectiveness of planning software. To achieve the aimed of this study, the following objectives has been identified such as to study the scheduling technique used in developing planning and scheduling, to identify the factors that cause the importance of using planning software for contractors nowadays and to analyses level of the effectiveness of using planning software in delivering construction projects. This study involved contractor who have project in the area of peninsular Malaysia. This study is carried out by questionnaires. A total of 50 questionnaires were distributed and only 46 questionnaires were returned was answered. This study was found that type of constructions that most involved in planning and scheduling software in building construction. The technique that the most used in schedule and cost planning and control was using software for schedule management. The main factor of using planning software was to get budget and work time for each activity and aimed to achieving an effective project planning. Planning and scheduling software more effectiveness because of it would be easily to share information and stay up-to-date with project changes and also time saving of construction work can be improve from software planning.